Digitalisasi Proses Penjualan pada Rumah Makan Sederhana Melalui Perancangan Sistem Informasi Penjualan Berbasis Web - Aditya Saputra; Rangga Auditia; Yeldina Kathelina (CV. Shofanah Media Berkah, 2025)
The rapid development of information technology encourages culinary businesses, particularly small restaurants, to adopt digital systems in order to improve operational efficiency. However, many small restaurants still manage their sales processes manually, which can lead to data recording errors, data loss, and delays in generating sales reports. This study aims to design and implement a web-based sales information system for small restaurants that can manage menu data, orders, transactions, and sales reports in an integrated manner. The research method applied is Research and Development (R&D) using the Rapid Application Development (RAD) approach, which consists of requirement planning, system design, construction, and implementation stages. The developed system provides features such as user authentication, menu management, sales transaction processing, and automated sales reporting. System testing results indicate that all features function properly and meet user requirements. Therefore, the proposed web-based sales information system is able to improve sales process efficiency, transaction data accuracy, and service quality in small restaurant operations.